A benders-decomposition-based transient-stability-constrained unit scheduling model utilizing cutset energy function method. (January 2021) - Saberi, Hossein; Amraee, Turaj; Zhang, Cuo; Dong, Zhao Yang
Highlights: Proposing an energy-based transient stability constrained unit commitment model. Considering sensitivity of generation level and inertia on stability margin. Proposing cutset energy function methodology without loss of network structure. Developing a state transition MILP formulation for the unit commitment model. Abstract: Rapid growth of load demand and concurrently system inertia deterioration put power systems at risk of transient instability. Therefore, operation of power systems as bulk complex systems must be secured against transient instability not only in hourly optimal power flow studies, but also in daily unit scheduling. To address this challenge, in this paper, secure and economic operation of power system is ensured through a Transient Stability-Constrained Unit Commitment (TSCUC) model employing Benders Decomposition (BD) technique. The proposed TSCUC model consists of one master problem determining committed units and two distinct sub-problems verifying the steady state impacts of single outages, and transient stability criteria, respectively. This paper proposes a state transition formulation for master problem as a mixed integer linear programming optimization problem preserving both compactness and tightness of the problem. A structure-preserving transient stability assessment approach called cutset energy function method is developed to assess the transient stability of the system for each configuration of the committed units, under a set of probable contingencies. Several case studies on a dynamic test system are demonstrated to validate the efficacy of the proposed TSCUC algorithm. Finally, the proposed method performance is compared with the state-of-the-art methods.